2021
DOI: 10.3390/molecules26175314
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Insight of Pyrrolylated-Chalcones as New Anti-Methicillin-Resistant Staphylococcus aureus (Anti-MRSA) Agents

Abstract: Bacterial infections are regarded as one of the leading causes of fatal morbidity and death in patients infected with diseases. The ability of microorganisms, particularly methicillin-resistant Staphylococcus aureus (MRSA), to develop resistance to current drugs has evoked the need for a continuous search for new drugs with better efficacies. Hence, a series of non-PAINS associated pyrrolylated-chalcones (1–15) were synthesized and evaluated for their potency against MRSA. The hydroxyl-containing compounds (8,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…To further validate the in-silico results, ( E )-3-(3,5-difluorophenyl)-1-(1 H -pyrrol-2-yl)prop-2-en-1-one (compound 8 ) was selected for synthesis. Compound 8 was chemically prepared by a one-pot base-catalyzed Claisen-Schmidt condensation reaction [ 21 ] and structurally characterized using X-ray crystallography technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further validate the in-silico results, ( E )-3-(3,5-difluorophenyl)-1-(1 H -pyrrol-2-yl)prop-2-en-1-one (compound 8 ) was selected for synthesis. Compound 8 was chemically prepared by a one-pot base-catalyzed Claisen-Schmidt condensation reaction [ 21 ] and structurally characterized using X-ray crystallography technique.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis was adapted based on [ 21 ], where the predicted active antiepileptic chalcone, compound 8 , was synthesized by a one-pot Claisen-Schmidt condensation reaction, purified and structurally characterized single crystal X-ray diffraction technique. Synthetically, 2 mmol of 2-acetylpyrrole (0.22 g) and 3,5-difluorobenzaldehyde (218 μL) were dissolved in 5 mL of 95% ethanol and the mixture was stirred for 5 min, followed by the dropwise addition of 1 mL of NaOH (6 M).…”
Section: Methodsmentioning
confidence: 99%
“…ADMET investigation revealed that these compounds are non-toxic and exhibit a high rate of oral absorption. Although allosteric site inhibition against doubly mutant PBP2a was explored using quinazolinone (QNZ) pharmacophore screening, it exhibited lower binding affinity compared to the reported molecules mentioned below [148][149][150].…”
Section: Non-β-lactam Allosteric Inhibitorsmentioning
confidence: 99%
“…Figure 11. (A) Novel structure of 1,2,4-Oxadiazole-containing derivatives[150]. (B) Synthesis route for 1,2,4-oxadiazole-containing derivatives.…”
mentioning
confidence: 99%
“…Chalcone analogues have been reported with a wide range of biological activities, including anti-inflammatory, antimicrobial, and anticancer properties (Kar Mahapatra et al, 2019;Lin et al, 2002;Nowakowska, 2007). Recently, we discovered a new promising anti-microbial candidate, 3-(3hydroxyphenyl)-1-(1H-pyrrol-2-yl)prop-2-en-1-one (3HPPP), which showed remarkable inhibitory activity on methicillin-resistant Staphylococcus aureus (MRSA, ATCC 700699) with MIC and MBC values of 0.23 mg ml À1 and 0.47 mg ml À1 , respectively (Gunasekharan et al, 2021). However, as yet the crystal structure of this compound has remained elusive.…”
Section: Chemical Contextmentioning
confidence: 99%